Media visit to Climate Smart Villages, Karnal Haryana - CGIAR Research Program on Climate Change, Agriculture and Food Security (2014)
Journalists from leading media houses visited Climate Smart Villages in Karnal Haryana. Climate Smart Villages are sites where researchers, local partners and farmers come together to identify the most suitable climate smart agriculture interventions for a particular location. CIMMYT scientists ML Jat and Surabhi Mittal also participated in the visit and interacted with journalists.